Digestibility of diets with growing levels of defatted coconut flour in growing rabbits - Acosta-Acosta, Yanixi; La-O-Michel, Ángel Luis; Valdivié-Navarro, Manuel Isidoro; Cantalapiedra-Bello, Jaqueline (Universidad Pedagógica y Tecnológica de Colombia, 2018)
In order to evaluate the influence of defatted coconut flour on the apparent digestibility coefficients (ADC) of nutrients for growing rabbits, five diets were elaborated with increasing levels of defatted coconut flour (0 %, 10 %, 20 %, 30 % and 40 %). The diets were given to 50 Chinchilla rabbits, distributed in a totally randomized design, with an experimental period of 12 days. The ADC of the dry matter (MS), gross protein (PB), gross fiber (BFC), organic matter (MO) and ash (Czs) were determined. The inclusion of defatted coconut flour into the rabbit’s diet had not effect on the ADC of MS, with average values close to 60 %. High values of ADC of PB were observed (74.92 % and 77.86 %), which decreased for levels of defatted coconut flour of 30 % and 40 %. The ADC of BFC behaved similar to the PB, with mean values between 44.66 % and 49.80 %. The rabbits showed a good use of the ash content with ADC from 66.80 % to 72.99 %, which were more elevated for diets with 0 % and 10 % of defatted coconut flour. The results indicate that the rabbits carried out a high absorption of the inorganic compounds.